Menangani Kebersihan Area Kitchen dan Kelengkapan Alat-alat Memasak di Hotel Best Western Premier Hive (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2022)
In processing food to achieve speed and accuracy of kitchen operations, it will be supported by kitchen equipment. In achieving a goal of increasing productivity stability, by equipping supporting and sufficient equipment. Considering that kitchen operations must run smoothly, the role of a tool is very important in the production process where the production value of equipment perfection. equipment damage due to the weakness of its users, for that equipment must be maintained and maintained properly so as not to experience severe damage that will hamper various activities inside. Kitchen employees who are implementers of the food processing production system using utensils should be considered for operating them. It really requires an understanding of employees about equipment both large and small, and how to use it properly and the function of each of these equipment. the results of observations, interviews, and questionnaires conducted by the author at Best Western Premier Hive.